A(nother) time for nature? Situating non-human nature experiences within the emotional transitions of sight loss. (May 2021) - Bell, Sarah L.; Foley, Ronan
Abstract: Sight impairment is experienced by approximately 253 million people worldwide, including people of all generations, at all life course stages. Caught between past and present embodiments of the world, people often express feelings of loss with the onset of sight impairment. This paper examines the role of nonhuman nature encounters as a contingent resource amongst individuals navigating these emotional transitions. It responds to recent calls to attend to the life course in both critical disability studies and the growing body of work linking nonhuman nature relations to human wellbeing. The paper draws on findings from a qualitative study that combined in-depth narrative interviews with in situ go-along interviews to explore how 31 people with sight impairment in England describe and experience a sense of wellbeing (or otherwise) with nature across their everyday lives and life trajectories. The data were analysed using inductive narrative thematic analysis. While nonhuman nature encounters were valued by many participants in promoting a sense of freedom, relatedness, pleasurable sensory immersion, opportunities for exploration and 'skilling up', this paper cautions against generalised or overly Romantic tropes of what nonhuman nature can 'do' through key sight loss junctures, and for whom. It highlights the value of providing timely and sensitive social scaffolding and nurturing creativity to open up meaningful opportunities to engage with nonhuman nature and to counter feelings of loss exacerbated by identity-limiting life course narratives and disability stereotypes. Informed by the stories shared by participants to chart and situate their experiences of sight loss, we call for a new identity politics within and beyond the growing movement to 'connect' people to nonhuman nature for wellbeing; a politics that affirms diverse forms of more-than-human embodiment, recognising how and why such relations may weave into – and indeed out of – people's varied, interdependent life course trajectories. Highlights: Disabling life course norms can exacerbate feelings of loss with sight impairment. Care is needed in generalising benefits of nature through transitions of sight loss. Social scaffolding and creativity can enable supportive nonhuman encounters. A more inclusive identity politics is needed in nature-wellbeing policy & practice.